A study on Ami Probashi, a project of the Bangla Trac group, to curb manpower fraud in foreign employment: digitalization in Bangladesh's labor migration process with more satisfaction - Das, Shubhojit (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.